Labour supply disincentive effects of old age public pensions: A case study for West Germany combining panel data and aggregate information - Sikandar Siddiqui (Universität Konstanz, Forschungsschwerpunkt Internationale Arbeitsmarktforschung, 1995)
In this paper, the impact of the West German pension system on the retirement decisions of elderly citizens is analyzed within the framework of a discrete-time hazard rate model deduced from a micro-economic decision rule. The model is estimated using a balanced panel of elderly West German citizens. In order to improve the precision of the estimates obtained, the data from the sample are combined with aggregate-level information on the labour force participation behaviour of the elderly. Policy-related simulation experiments based on the estimates reveal that the probability of early retirement can be reduced significantly by appropriate changes in the pension system.
Keywords: C32; C41; J26; 330; Arbeitsangebot; Altersgrenze; Gesetzliche Rentenversicherung; Deutschland